2002
DOI: 10.1128/mcb.22.11.3942-3957.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interferon Regulatory Factor (IRF), IRF-10, Has a Unique Role in Immune Defense and Is Induced by the v-Rel Oncoprotein

Abstract: The cloning and functional characterization of a novel interferon regulatory factor (IRF), IRF-10, are described. IRF-10 is most closely related to IRF-4 but differs in both its constitutive and inducible expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 109 publications
6
66
1
Order By: Relevance
“…As reported in our previous study [26], IRF10 gene was identified in this study in all other major groups of vertebrates, except in most primate and rodent species in which IRF10 appears only as a pseudogene or is overlapped with the downstream DUSP15 gene [25,26], although more genomic sequences of vertebrates have been released and searched (see Supplemental Table 1 and [26]). To our surprise, a transcript encoding IRF10 was found in O. garnettii genome database.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…As reported in our previous study [26], IRF10 gene was identified in this study in all other major groups of vertebrates, except in most primate and rodent species in which IRF10 appears only as a pseudogene or is overlapped with the downstream DUSP15 gene [25,26], although more genomic sequences of vertebrates have been released and searched (see Supplemental Table 1 and [26]). To our surprise, a transcript encoding IRF10 was found in O. garnettii genome database.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, Euarchontoglires have a rather conserved gene synteny, as observed in genomic regions flanking the IRF10 gene in chicken and frog, implying that IRF10 genes might have been lost during the evolution in primates and rodents, but the origin of IRF10 might have occurred at least prior to the divergence of teleost and tetrapod lineage. On the other hand, it is reported that IRF10 has an important role in host defense in fish and birds [25,27,28]. The absence of IRF10 in some mammalian species may reflect the redundancy of its function or the compensation by other genes during evolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations